العقبة الابستمولوجية عند غاستون باشلار وإسقاطها على العقل العربي - جعفورة, مصعب; تهامي, محمد (جامعة الوادي - University of Eloued, 2023)
يهدف هذا المقال إلى تسليط الضوء على إسهامات أحد عمالقة الإبستمولوجيا الفرنسي غاستون باشلار من خلال التركيز على فكرته حول العقبات الابستمولوجية التي ناقشها في إطار حديثه عن مسألة "تكوين العقل العلمي''. لهذا سنحاول اسقاط مفهوم العقبة الابستمولوجية على أحد ملامح الفكر العربي في المرحلة الراهنة من خلال هاجس المؤامرة أو كما تعرف بــ '' نظرية المؤامرة''، والتي أصبحت تعبر عن أزمة الإبداع الموجودة في الخطاب العربي المعاصر-كما يرى الجابري- لذا فإننا نعتقد أن تبني أطروحة نظرية المؤامرة عند بعض الأكاديميين يمثل صورا عدة للعقبات المعرفية، ولقد ارتأينا أن نضع أطروحة "نظرية المؤامرة" كمثال واقعي يمكن أن يكون شارحا لفكرة الابستمولوجيا الباشلارية حول العقبة، لهذا سنركز على العائق اللفظي وعائق المعرفة العامة ( التعميم ). وقد خلصنا إلى أن نظرية المؤامرة باعتبارها عقبة أبستمولوجيا تمثل أحد أهم المخاطر المعرفية الي تواجه العقل العربي المعاصر لما تتميز به من تلك الاختزالية التي ترُد الفكر إلى مستوى ضيق من المفاهيم وتعطل رؤية ما ليس مفكرا به. Abstract: This article aims to highlight the contributions of one of the greatest epistemologists, the French „Gaston Bachelard‟ through focusing on his idea about the epistemological obstacles that he discussed in his talking about the issue of “the formation of the scientific mind”. For this we will try to contrast the concept of the epistemological obstacle on one of the features of the Arab Thought at the current time through the premonition of conspiracy or as it is known as “conspiracy theory”, which has become an expression for the creativity crisis in contemporary Arab discourse - as Al-Jabiri contemplates- so we believe that the adoption of the conspiracy theory thesis among some academics represents several images for the cognitive obstacles, and we decided to put the thesis of “conspiracy theory” as a realistic example that can explain the idea of the Bachelardian epistemology about the obstacle, for this we will focus on the verbal obstacle and the obstacle of general knowledge (Generalization.) We have concluded that the conspiracy theory as an epystemological obstacle represents one of the most important cognitive risks facing the contemporary Arab mind due to its reductive factor that retreats the thought to a tight level of concepts and smolders seeing what is not thought of.
نظرية المؤامرة نموذجا
مقال
Keywords: عقبة إبستمولوجية ; غاستون باشلار ; نظرية المؤامرة ; فكر عربي; epistemological obstacles; Gaston Bachelard ; conspiracy theory; Arab Thought